Can US welfare programs cure persistent poverty? - Ulimwengu, John M. (International Food Policy Research Institute, 2008)
A simple dynamic panel model is used to capture persistence in poverty. This simple model allows a more accurate derivation of the permanent level of the measure of well-being from which persistent poverty is defined. Using a longitudinal dataset from the United States of America, the results show that the variability of the measure of welfare (logarithm of income-to-needs ratio) is mainly driven by transitory shocks through unobservable individual and time-specific characteristics. Consequently, means-tested schemes such as food stamps or the Temporary Assistance to Needy Families (TANF) block grant program can easily miss genuinely eligible welfare clients. The results also suggest that the probability of exiting persistent poverty is much higher for job participants than welfare programs participants. However, compared to their employed counterparts, unemployed individuals have little or no chance of escaping persistent poverty unless they choose to participate in welfare programs.